On a Vendor-Buyer Integrated Inventory Model with Different Co-Ordination Levels - Pandian, P.; Dhivya Lakshmi, M. (International Journal of Engineering and Technology, 2018)
An integrated inventory model with different co-ordination levels for a vendor and a buyer is proposed in this paper. The optimal policies for the proposed model are obtained. Numerical example of the developed model is presented and analyzed.Â Â